Alteration of intestinal mucosal microbiota in mice with Chinese dampness-heat syndrom diarrhea by improper diet combined with high temperature and humidity environments - Qiao, Bo; Li, Xiaoya; Peng, Maijiao; Hui, Huaying; Tan, Zhoujin (Frontiers in Cellular and Infection Microbiology, 2023)
Background Environment, diet, and emotion may trigger diarrhea, but the mechanism is unclear. Dietary habits or environmental factors affect the composition of gut microbiota. This study aimed to investigate the effects of improper diet combined with high humidity and temperature (HTH) environment on the intestinal mucosal microbiota. Materials and methods Kunming mice were randomly assigned to two equal groups of five mice, namely the control (ccm) group and the model (cmm) group. Diarrhea mice with dampness-heat (DSH) were established by improper diet combined with HTH environments. We used 16S rRNA gene amplicon sequencing to analyze the characteristics of intestinal mucosal microbiota and the interaction relationship of function. Results Our study shows that the intestinal mucosal microbiota of mice changed significantly after an improper diet combined with the HTH environments. The abundance of Fusobacteria and Haemophilus increased dramatically in the cmm group compared to the ccm group (P<0.05). And the abundance of Firmicutes, Lactobacillus, and Lonsdalea was significantly decreased in the cmm group (P<0.05). According to the functional predictive analysis, we found that Lactobacillus showed a significant negative correlation with Protein export, Homologous recombination, Phenylalanine, tyrosine, tryptophan biosynthesis, Citrate cycle, and Lipoic acid metabolism. Conclusion Diarrhea with DSH constructed under improper diet and HTH environment may be related to Lactobacillus and Haemophilus. And long-term consumption of improper diet and the HTH environment may affect metabolism.